Shaping Health Habits of Early School Children in The Context of Sustainable Education - Waszczuk, Joanna; Konowaluk-Nikitin, Helena; Pawłowicz-Sosnowska, Ewa (Studia Ecologiae et Bioethicae, 2021)
In the current literature on the subject the theoretical concepts of sustainable development are fairly well documented, there is however a need to research the applications of those ideas in practice. It seems important then to build strategies of actions especially concerning the realm of consciousness. A necessary condition for shaping social consciousness of sustainable development is shaping pro-health attitude of children as soon as in early school. That is why, the goal of the study, whose results have been presented in this article, was to inspect the level of pro-health habits achieved by early school children in the course of sustainable education. An analysis of the results allowed to answer the key problem question: “How is pro-health attitude of early school children shaped in the context of sustainable development, with the influences of parents and teachers?” The results of the study showed a high level of pro-health habits in children, which to some degree points towards a need to keep up the strategy of actions of sustainable education by executing tasks in the aspect of cooperation of school and family environments, and also a need to continue research in the aforementioned territory.